Climate change and topographic differences influence grassland vegetation greening across environmental gradients - Xun, Qilei; An, Shazhou; Lu, Mingzhi (Frontiers in Environmental Science, 2024)
Despite the research on the responses of grassland vegetation to climate change and topography has advance worldwide, the large-scale importance of these parameters to grassland vegetation greening in arid regions across environmental gradients is unclear. To address this, in this study, we applied MODIS Normalized Difference Vegetation Index (NDVI) data and trend analysis methods to measure the spatial-temporal variation in grassland vegetation greening in central Eurasia. Multiple regression models and hierarchical partitioning were used to quantify the importance of climate (annual precipitation [AP], annual mean temperature [AMT], relative humidity [RH]) and topography (elevation [ELE], aspect [ASP], topographic position index [TPI]) to the NDVI. The results showed that there was a significant increasing trend in the NDVI of meadows, but not other grassland types, from 2000 to 2021 (3.3 × 10 -3 /year, P < 0.05). Additionally, the responses of the NDVI to climate and topography in deserts were positively correlated with RH, AP, and ELE. Meanwhile, the dependence of NDVI on climate and topography decreased with increasing RH. Under conditions of escalating AMT and AP, RH and ELE independently contributed to explaining the NDVI. However, RH may be the key determinant of long-term NDVI stabilization in arid grassland. These findings underscore the significance of vegetation-climate-topography feedback and can inform the development of more comprehensive and effective climate mitigation and adaptation strategies.